THE EFFECT OF TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE OF PT. YOROZU AUTOMOTIVE INDONESIA - Mahdiyyah Indah Hasica; Aji Tuhagana; Zenita Apriania (Journal Of Resource Management, Economics And Business, 2024)
Purpose: This research aims to evaluate the potential for increasing employee performance at PT. Yorozu Automotive Indonesia through training and career development efforts. Research Methodology: A quantitative descriptive approach was used in this study, involving statistical analysis such as multiple linear regression, coefficient of determination, hypothesis testing (t), and simultaneous testing (F). Data was collected by distributing questionnaires to 64 participants. Results: The results of the partial analysis show that the tcount value for training (61.188) and career development (21.319) exceeds the ttable value (1.998), indicating a significant influence of both variables on employee performance. Furthermore, the simultaneous test shows that the Fcount value (8370.830) far exceeds the Ftable value (3.998), confirming that both training and career development simultaneously have a significant influence on employee performance in the operator department. The training and career development variables show the ability to have an influence on employee performance of 1,000, or an R Square of 100%. Limitations: The study only focused on the influence of training and career development on employee performance at PT. Yorozu Automotive Indonesia Contribution: The findings provide insights for management on the importance of providing effective training and career development programs to improve employee performance in the automotive manufacturing industry.